EFFECT OF FINANCIAL LITERACY AND LOCUS OF CONTROL ON MSME PERFORMANCE IN MAESAN DISTRICT, BONDOWOSO REGENCY - Arini Dinan Haq; Misbahul Munir (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
Quantitative method. A sample of 100 MSME actors using non-probability sampling technique and proportional stratification allocations were divided into 90 micro businesses, 9 small businesses and 1 medium business. The collection tool is in the form of a questionnaire. Data analysis used SPSS 23 multiple linear regression. The results of the study stated that financial literacy had a significant positive effect on financial performance, while locus of control had no effect on MSME financial performance. And simultaneously there is a positive and significant influence between locus of control and financial literacy on the financial performance of MSMEs in Maesan District, Bondowoso.